Resistance prediction of amphibious boat in calm water using computational fluid dynamic approach / Nabilatul Athirah Misnan - Misnan, Nabilatul Athirah (2022)
Humans' continual exploration of space has resulted in significant breakthroughs in marine and terrestrial technology. As one of the world's most populous countries, China has many rivers and lake. There are almost 1500 rivers in China with a drainage area. There are over 2800 lakes and over one hundred coastal bays in the area. The drainage area is home to the ethnic group. Water and land transportation is in high demand from people worldwide as society develops. Rather than being intended for land transport with the capacity to cross water, amphibious vehicles are designed for water transport with the ability to go on land. The difference is that the vehicles are meant to be high performing on water, with land movement provided as a bonus feature rather than as the primary role.